CDMOs Play a Critical Role in the Biopharmaceutical Ecosystem - Kurata, Hideyuki; Ishino, Tetsuya; Ohshima, Yasuhiro; Yohda, Masafumi (Frontiers in Bioengineering and Biotechnology, 2022)
Biopharmaceutical industries have advanced significantly after the millennium. Novel biopharmaceuticals have been developed one after another, and blockbuster drugs have been produced. Accompanying the increase in the demand for biopharmaceuticals, a business model called “contract development manufacturing organization (CDMO)” has emerged. A CDMO is entrusted with the development and manufacturing of production processes from pharmaceutical companies. In this review, we identify the success factors of the biopharmaceutical CDMO by comparing the CDMO with the foundry business for the semiconductor industry. Furthermore, we also review monoclonal antibody production platforms and new technologies that are critical aspects of differentiation strategies in the biopharmaceutical CDMO.